2015
DOI: 10.1016/j.amsu.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Induction of continuous expanding infrarenal aortic aneurysms in a large porcine animal model

Abstract: BackgroundA large animal model with a continuous expanding infrarenal aortic aneurysm gives access to a more realistic AAA model with anatomy and physiology similar to humans, and thus allows for new experimental research in the natural history and treatment options of the disease.Methods10 pigs (group A) underwent infrarenal aortic dissection, balloon dilatation, infusion of elastase into the lumen and placement of a stenosing cuff around the aorta. 10 control pigs (group B) underwent a sham procedure. The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 14 publications
2
23
0
Order By: Relevance
“…41 Kloster et al recently reported a continuously expanding AAA over 28 days in a porcine model. 42 They performed elastase infusion followed by angioplasty and cuff placement proximal to the AAA (Fig. 4).…”
Section: Non-rodentsmentioning
confidence: 99%
“…41 Kloster et al recently reported a continuously expanding AAA over 28 days in a porcine model. 42 They performed elastase infusion followed by angioplasty and cuff placement proximal to the AAA (Fig. 4).…”
Section: Non-rodentsmentioning
confidence: 99%
“…This substantial AP-diameter increase is far beyond what can be attributed to normal increase in body weight of the pigs as shown by the control pigs in our recent study by Kloster et al. [8] This study was performed at the same institution using pigs from the same herd and at the same age as in our study. Kloster et al.…”
Section: Discussionmentioning
confidence: 99%
“…It is percutaneously performed and whole side branches of aorta are preserved. It results with moderate degree of dilatation [2].…”
Section: Balloon Dilatationmentioning
confidence: 98%
“…Most important advantage of this model is preservation of lumbar arteries. Disadvantages are requirement of laparotomy, occurrence of retroperitoneal fibrosis and aneurysm extension limited at proximal [2]. Turbulent flow in this model provides appropriate hemodynamic effect for damaging intercellular matrix after protective barriers like tunica intima and lamina elastic interna are weakened by elastase and effect of balloon; rather than creating aneurysm alone [45].…”
Section: Stenosing Cuffmentioning
confidence: 99%
See 1 more Smart Citation